(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The research statement to the amount of the contribution of information and communication technology in the quality of tourism and hotel services, and determine the relationship between the impact of information and communication and the quality of tourism services technology, The importance of the research is to establish the philosophical thinking of the nature of variables, as a modern administrative terminology and employ them towards the quality of tourism and hotel services, the research dealt with a problem expressed by a number of intellectual and practical questions, Was formulated based on the current situation witnessed by the tourism sector and hotel in Iraq, and the real gap was the lack of awareness of the importance of the variables studied, and to achieve the above, The researcher developed a virtual model based on documentation and task assignment that was adopted in the formulation of two hypotheses based on the research problem and its questions in order to achieve the purposes of research. The research was based on a descriptive and analytical approach. The researcher designed the questionnaire. The research community consisted of a selection of selected hotels in the Iraqi capital Baghdad. A random sample of (61) of the guests residing in the surveyed hotels was selected. The sample was 20% according to the hotel records. The study came out with theoretical and practical conclusions, which identified the reality of the variables investigated in the environment In light of this, a number of recommendations have been made. The most important of these recommendations is the emphasis on the importance of the variables examined to increase the quality of the services provided, through which they can acquire the largest market share.